Development of Ukrainian enterprises in crisis economy in brand management system - Maiboroda, Hanna; Майборода, Ганна Олександрівна; Майборода, Анна Александровна; Marchuk, Anastasiia; Марчук, Анастасія Олександрівна; Марчук, Анастасия Александровна (My University, 2021)
The purpose of the article is to improve and deepen the theoretical aspects of brand value assessment methods, highlighting their advantages and disadvantages, combining existing techniques for more effective assessment of the enterprise, the practical calculation of the brand value "Kyivhlib" on the example of the Ukrainian enterprise-leader of the baking industry. In the article the theoretical analysis of publications, which considered the main aspects of the brand management system at the enterprises, in particular domestic ones, was carried out. The authors also highlighted the subject of the research, which is the given factors and structural elements of brand identity and value from the side of strategic activities of companies that operate in two Ukrainian markets – the market of milk and dairy products and the market of bakery and bakery products. Methodology. To determine the brand value was chosen one of the enterprises in the bakery industry, located in Kyiv – "Kyivhlib". The calculation was carried out using a combination of methods "Interbrand Model" and the method of royalty based on the data of the public accounts of the enterprise for 2019. Determination of the index of the brand role was carried out by expert method using seven basic criteria (leadership, stability, market, internationality, trends, support, protection). The last step was the calculation of the final brand value, where the brand profit is defined as the product of the intangible profit value and the brand role index. Also to calculate the final brand value, it was necessary to calculate the discounted cash flows over the years of the economic life of the investment. Results. As a result the index of brand role added up to 86%. As for "Kyivhlib" it was determined that the brand multiplier value of 18,8 corresponds to a point estimate of brand strength (86 points). The results obtained by using the method based on "Interbrand" model showed that brand value of "Kyivhlib" is at the level of 5093,1 thousand UAH. Due to the fact that this model involves a large number of subjective estimates, the results may differ from the calculations obtained by using other methods and models. Practical implications. The value of the brand affects both the financial aspects of the enterprise and its non-financial side. It is worth noting that the brand is an intangible asset but it provides a real financial result in the form of profit. That is why companies, seeking to gain a leading position in the market, should pay close attention to assessing the brand value and using the obtained data in strategic management.
Keywords: brand management; bakery industry; marketing communications; promo calenda; brand multiplier; brand value